Brief Report: Ordinate Scaling and Axis Proportions of Single-Case Graphs in Two Prominent EBD Journals From 2010 to 2019. (February 2022) - Peltier, Corey; McKenna, John W.; Sinclair, Tracy E.; Garwood, Justin; Vannest, Kimberly J.
Single-case experimental designs (SCEDs) are frequently used to evaluate whether a functional relation exists between interventions and student outcomes. A critical factor in decision making is the evaluation of graphical data, typically displayed in time-series graphs. Distortion in the graphical display of data can lead to invalid decisions on whether a functional relation exists, as well as overestimating the magnitude of an effect. Previous research has identified two potentially analysis-altering elements that when manipulated alter visual analysts' decision regarding the presence of a functional relation and magnitude of effect. The purpose of this review was to evaluate the graphical display of data from SCEDs in the field of emotional and behavioral disorders (EBD). The review covered 40 SCEDs, including 258 graphs, published in Behavioral Disorders and Journal of Emotional and Behavioral Disorders over the last 10 years (2010–2019). We identified large variation in the axis proportions of reviewed graphs, as measured using standardized x:y and the data points per x - to y -axis ratio (DPPXYR). A majority of graphs included an ordinate scaling procedure that aligns with findings from preliminary research on this analysis-altering element. We provide recommendations to the field on designing graphs to enhance the validity of visual analysis.